Family expressiveness and relation to birth order among Chinese young adults in Universiti Malaysia Sabah: A preliminary analysis - Chew, Ying Hui; Grace Wong Ying Heng; Tan, Pyn Ting; Chao, Tung Yin; Walton Wider (Universiti Malaysia Sabah, 2016)
A scant research has examined the links between the degree of family expressiveness and relation to birth order. In this preliminary study, we examined a sample of 45 Chinese young adults and grouped them into three different birth orders (15 first-born, 15 middle-born, and 15 late born). The Chinese young adults completed the Family Expressiveness Questionnaire (FEQ) which contain 40-item to assess the emotional expressiveness towards one’s family of origin. The Expressiveness subscale measures the extent to which family members openly and directly express their emotions. Results indicated that Chinese young adults in Universiti Malaysia Sabah (UMS) have greater frequency and intensity of positive submissive. Furthermore, the family expressiveness among first-born child and later-born child scored highest in the positive submissive, whereas the middle-born child scored highest on positive dominant.